Biomechanical Analysis of the User's Movements during Tactile Interaction: Postures of Older Aged Users' Wrists - Ader, Lilian Genaro Motti Ader; Vigouroux, Nadine Vigouroux; Gorce, Philippe Gorce (Teste; 2018: 2018, 2018)
With the emergence of devices equipped with touchscreen, it is necessary to understand the difficulties older aged adults find for executing the gestures of tactile interaction in order to prevent the digital exclusion of this group of users. The association of the analysis of the users' movements to the study of their interaction with touchscreen provide additional information for the interpretation of the results. In the present study, we recorded the movements of older and younger adults during interaction with a tablet, horizontally placed on a desk. We identified differences in the characteristics of the postures of the users' wrists, particularly a greater angular amplitude for older participants which could explain the longer times and the increased number of errors for this group of users. In this paper, we discuss the usability of tactile interaction from an ergonomic perspective.